Histological Evaluation of the Effect of Metronidazolemedicine on the Brain Tissue in Adult Female White Rats - Yaseen Khalaf Mohammed1 , Ayad Hameed Ibrahim2 , Aziz Khalid Hameed3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study was undertaken to assess the neurotoxic effect of metronidazole in pregnant female rats . Twenty adult pregnant female rats were randomly divided into four groups treatment with oral metronidazole at the therapeutic dose 250 mg/kg, 500 mg/kg and 1000 mg/kg from the eight day of pregnant to the twenty day of pregnant (every eight hour), whereas the last group serve as a control. Routine Histological Techniques were done and stained by Hematoxylin and Eosin (H & E). The histopathological examination of brain show the lesion was characterized by a wide spongy cavitation and cavitation was observed around the nerve and glial cells along with atrophy of some of its nuclei and around the axonal and vascular axons with the presence of nuclear thickening of some glia cells, as well as hyperplasia of the glial cells supporting, disintegration and degeneration of nerve fibers, with damage to the meninges. In addition to the presence of bloody congestion. This study revealed that metronidazole have a neurotoxic effect in adult female rats with a severity depended on its dose and duration of administration.